The Effect of Short Term Debt To Profitability In The Pratama Clinic of Kosasih Rajabasa (Kosasih Group) - Saputri, Pertiwi Dwi Anggraeni; Fitriyana, Eka; Yusoff, Murni (Bina Bangsa International Journal of Business and Management, 2021)
This study aims to determine whether debt, both simultaneously and partially, affects the profitability of the Pratasih Rajabasa Primary Clinic (Kosasih Group) for the 2016-2018 periods. After conducting a regression analysis using SPSS version 23.0 it can be seen that the constant value of 12.725, which means if short-term debt (X) equals zero or fixed, then profitability (Net Profit Margin) also remains at 12.725. The coefficient of short-term debt (X) of 9,844 shows that if short-term debt has increased by one unit (1.00) then profitability (Net Profit Margin) will experience an increase or increase of 9,844. Based on the partial hypothesis test results can be seen that short-term debt has a significant effect on profitability (Net Profit Margin). This is evident from the results of the t test, where short-term debt has tcount> t table which is 2.902> 2.0322 with Sig. <α is 0.006 <0.05. Thus it can be concluded that there is a significant effect between short-term debts on profitability (Net Profit Margin) at the Pratama Kosasih Rajabasa Clinic (Kosasih Group) for the period of 2016-2018